A Multilevel Field Investigation of Emotional Labor, Affect, Work Withdrawal, and Gender - Scott, Brent A.; Barnes, Christopher M. (Academy of Management Journal, 2011)
Using experience-sampling methodology, we examined within-individual relationships among emotional labor, negative and positive affective states, and work withdrawal, as well as the moderating role of gender. Fifty-eight bus drivers completed two daily surveys over a two-week period, producing 415 matched surveys. Results of hierarchical linear models revealed that affective states worsened when employees engaged in surface acting but improved when they engaged in deep acting. Surface acting was positively associated with work withdrawal, and state negative affect mediated this relationship. Results also revealed moderating effects of gender: the within-individual relationships were stronger for females than for males.